Traduire en se décentrant : exemples d’écueils rencontrés par des étudiants en français de l’économie et de la finance - Piotrowski, Sebastian (Neofilolog, 2023)
This article focuses on the relationship between language and culture in the context of the translation of journalistic texts in economics and finance. We can assume that any text or discourse, whether literary or specialized, contains a number of culturemes, that is, elements at the interface of language and culture, typical of the given language, which pose translation difficulties. For the purposes of the article, translations made by students of Romance philology were analyzed and selected problems with the translation of culturemes, including the problem of adopting an appropriate deictic perspective, were highlighted. Another issue raised in the article is the hybrid nature of French media texts in economics and finance, which exhibit a large number of features typical of literary texts. The conclusion emphasizes the fact that students should be sensitized to those layers of text and discourse that are at the interface between language and culture. These layers must be properly identified, decoded and translated from the language of the source-culture to the language of the target culture.